Tentonin 3/TMEM150C regulates glucose-stimulated insulin secretion in pancreatic beta-cells - Wee, Jungwon; Pak, Sungmin; Kim, Tahnbee; Hong, Gyu-Sang; Lee, Ji Seon; Nan, Jinyan; Kim, Hyungsup; Lee, Mi-Ock; Park, Kyong Soo; Oh, Uhtaek (Cell Press, 2021)
Glucose homeostasis is initially regulated by the pancreatic hormone insulin. Glucose-stimulated insulin secretion in beta-cells is composed of two cellular mechanisms: a high glucose concentration not only depolarizes the membrane potential of the beta-cells by ATP-sensitive K+ channels but also induces cell inflation, which is sufficient to release insulin granules. However, the molecular identity of the stretch-activated cation channel responsible for the latter pathway remains unknown. Here, we demonstrate that Tentonin 3/TMEM150C (TTN3), a mechanosensitive channel, contributes to glucose-stimulated insulin secretion by mediating cation influx. TTN3 is expressed specifically in beta-cells and mediates cation currents to glucose and hypotonic stimulations. The glucose-induced depolarization, firing activity, and Ca2+ influx of beta-cells were significantly lower in Ttn3(-/-) mice. More importantly, Ttn3(-/-) mice show impaired glucose tolerance with decreased insulin secretion in vivo. We propose that TTN3, as a stretch-activated cation channel, contributes to glucose-stimulated insulin secretion.